CULTURAL INFLUENCES ON ROMANCE: A STUDY OF EXTERNAL FACTORS IN MAKOTO SHINKAI’S YOUR NAME - Ikhsan, Raka Muhammad; Azis, Safrudin; Rohmana, Wahyu Indah mala (Saksama: Jurnal Sastra, 2023)
The novel ‘Your Name’ by Makoto Shinkai is a popular Japanese romance story that revolves around the body swap phenomenon between two high school students, Taki and Mitsuha, who live in different places and have different backgrounds. The novel explores the psychological aspects of their relationship, such as their identity, personality, emotions, and communication, as well as the external factors that affect their romance, such as their culture, environment, and destiny. This research paper aims to analyze the romantic conflicts that arise from the psychological and external factors in the novel, and to examine their relevance in the lives of contemporary college students who may face similar challenges in their romantic relationships. The research method used is a qualitative approach, using Freud’s theory of personality The data sources are the novel itself and some related literature. The data analysis is done by identifying, categorizing, and interpreting the data based on the research questions and the theoretical framework. The results of the analysis show that the romantic conflicts in the novel are caused by the following factors: the id-ego-superego dynamics, the identity crisis, and the communication barriers. The research also finds that these factors are relevant in the lives of contemporary college students, who may experience similar conflicts in their romantic relationships due to the influence of globalization, technology, social media, and individualism. The research concludes that the novel ‘Your Name’ provides a realistic and relatable portrayal of the romantic conflicts that may occur in modern society, and that the novel can be used as a source of inspiration and guidance for college students who want to overcome their romantic problems and achieve a harmonious and fulfilling relationship.